Mesiodens with Impacted Inverted Supernumerary Tooth: A Rare Case Report - Avninder Kaur; Tshering Bhutia; Isha Sharma (Dental Journal of Advance Studies)
Supernumerary teeth (ST) occur in deciduous and permanent dentition, however, commonly occur in permanent dentition. Supernumerary teeth have a prevalence of 0.1–3.4%. Complications with this developmental anomaly can be minimized, if diagnosed and intervened early. A 9-year-old boy with an extra tooth in the front region reported to the OPD. The patient had mesiodens between his maxillary central incisors whereas radiographic examination revealed another inverted supernumerary tooth. Surgical removal of both the ST was done. Spontaneous correction of midline diastema was observed during follow-up period of 1 month.